A large diversity of non-rhizobial endophytes found in legume root nodules in Flanders (Belgium). (April 2015) - De Meyer, Sofie E.; De Beuf, Kristof; Vekeman, Bram; Willems, Anne
Abstract: We analysed the genetic properties of non-rhizobial root nodule endophytes (NRE) isolated from indigenous legumes in Flanders. In total, 654 isolates were obtained from 30 different plant species within the Faboideae legume subfamily. Partial sequencing of the 16S rRNA gene revealed a large diversity of different taxa from the classes Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Actinobacteria, Firmibacteria, Flavobacteria and Sphingobacteria. Many of the isolates belonged to the genera Bacillus (17.9%) and Pseudomonas (15.9%). No symbiosis ( nodC ) or nitrogen fixation related genes ( nifH ) could be detected amongst the isolates, which indicate the endophytic nature of the bacteria. Statistical analysis grouped the investigated plant species into six clusters according to the presence of particular NRE. However, no correlations could be found within these six clusters towards plant tribes or ecoregions the plants had been sampled from. Cluster analysis of the ecoregions according to the presence of NRE, revealed correlations between bacterial genera and those areas. However, groups present in the ecoregions did not correlate with the groups present in the different plant clusters. When combining our previous study on rhizobial diversity recovered from the same sampling campaign (De Meyer et al., 2011) with the current study, 84.1% of the isolates belonged to the traditional rhizobia groups and only 15.9% were NRE. The Loamy ecoregion yielded the lowest number of culturable NRE (8.04%) and the Campine ecoregion the highest number (24.19%). The present study highlights the frequent presence of these NRE in root nodules. The occurrence of certain rhizobia was correlated with the presence of particular NRE, suggesting their presence may not be accidental, however their functions remain unclear at this point. Highlights: Large diversity of non-rhizobial root nodule endophytes (NRE). Dominance of Bacillus and Pseudomonas species. No nodC and nifH genes detected. Correlation of NRE with sampled region in Flanders. Correlation between traditional rhizobia and NRE, with a dominance of rhizobia in the root nodule.